SB42 Side Event: Linking agricultural and climate change science and policy in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
On 6 June 2015 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) organized a side event at UNFCCC SBSTA Climate Change Conference in Bonn to share evidence and experience in addressing the impact of climate change and variability on smallholder farming, and solutions to tackle droughts, floods, pests and diseases in Africa. Photos: V. Meadu (CCAFS)